The Undue Influence Doctrine and Its Function in Consumer Financing Cases - Azam, Syaiful; Mulhadi, Mulhadi; Harianto, Dedi (Jurnal Media Hukum, 2020)
The practice of freedom of contract in Indonesia is remain imbalance due to unequal position of the parties. This imbalance has been used by companies to take advantages and at the same time harm consumers. This study aims to explain the "undue influence" doctrine in legal practice in Indonesia and its function in emphasizing the importance of the consensual principle in contracts. By using normative juridical approach based on secondary legal materials, statutory, and court decisions, and the data were collected through literature study and analyzed qualitatively. The terminology of undue influence or misbruik van omstandigheden in the Indonesian Civil Code obviously has not been regulated but has the same character as the concept of â€œdefect of the willâ€ as regulated in Article 1321 of the Code. The provision of â€œdefect of the willâ€ Â is an integral part of the consensual principle in Article 1320 of the Code. The function of this doctrine limits the application of the absolute principle of freedom of contract and becomes a source of law for judges in resolving contract disputes in court. In the reform of the national contract law, this doctrine should be considered to be included as an important element to complete main aspects of Article 1321 of the Code.